STUDY OF THE INFLUENCE OF WINDS IN THE POTENTIAL CONTAMINATION WITH HAZARDOUS SUBSTANCES AS A RESULT OF MAN-MADE ACCIDENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The report presents enterprises on the territory of Bulgaria that store or use in their production dangerous chemical, radiation and biological substances. An analysis was made of the substances used and the conditions for use and storage. In the event of an accident, these hazardous substances will pollute the environment. Wind plays a major role in dispersal of released substances and will determine the contaminated area. The direction and strength of winds at different altitudes in the settlements where these enterprises are located were studied. The obtained results were analysed based on the prevailing winds in the last 20 years.